Ledipasvir/sofosbuvir is effective and well tolerated in postkidney transplant patients with chronic hepatitis C virus. Issue 5 (25th March 2017) - Morales, Amilcar L.; Liriano‐Ward, Luz; Tierney, Amber; Sang, Michelle; Lalos, Alexander; Hassan, Mohamed; Nair, Vinay; Schiano, Thomas; Satoskar, Rohit; Smith, Coleman
Abstract: Patients with end‐stage renal diseases on hemodialysis have a high prevalence of hepatitis C infection (HCV). In most patients, treatment for HCV is delayed until postrenal transplant. We assessed the effectiveness and tolerance of ledipasvir/sofosbuvir (LDV/SOF) in 32 postkidney transplant patients infected with HCV. The group was composed predominantly of treatment‐naïve (75%) African American (68.75%) males (75%) infected with genotype 1a (62.5%). Most patients received a deceased donor kidney graft (78.1%). A 96% sustained viral response (SVR) was reported (27/28 patients). One patient relapsed. One patient with baseline graft dysfunction developed borderline rejection. No graft loss was reported. Six HIV‐coinfected patients were included in our analysis. Five of these patients achieved SVR 12. There were four deaths, and one of the deaths was in the HIV group. None of the deaths were attributed to therapy. Coinfected patients tolerated therapy well with no serious adverse events. Serum creatinine remained stable at baseline, end of therapy, and last follow‐up, (1.351±.50 mg/dL; 1.406±.63 mg/dL; 1.290±.39 mg/dL, respectively). In postkidney transplant patients with HCV infection with or without coinfection with HIV, a combination of LDV/SOF was well tolerated and effective.